Brain fog in long COVID limits function and health status, independently of hospital severity and preexisting conditions - Nordvig, Anna S.; Rajan, Mangala; Lau, Jennifer D.; Kingery, Justin R.; Mahmud, Meem; Chiang, Gloria C.; De Leon, Mony J.; Goyal, Parag (Frontiers in Neurology, 2023)
Importance The U.S. government has named post-acute sequelae of COVID-19 (longCOVID) as influential on disability rates. We previously showed that COVID-19 carries a medical/functional burden at 1 year, and that age and other risk factors of severe COVID-19 were not associated with increased longCOVID risk. Long-term longCOVID brain fog (BF) prevalence, risk factors and associated medical/functional factors are poorly understood, especially after mild SARS-CoV-2 infection. Methods A retrospective observational cohort study was conducted at an urban tertiary-care hospital. Of 1,032 acute COVID-19 survivors from March 3–May 15, 2020, 633 were called, 530 responded (59.2 ± 16.3 years, 44.5% female, 51.5% non-White) about BF prevalence, other longCOVID, post-acute ED/hospital utilization, perceived health/social network, effort tolerance, disability. Results At approximately 1-year, 31.9% (n = 169) experienced BF. Acute COVID-19 severity, age, and premorbid cardiopulmonary comorbidities did not differ between those with/without BF at 1 year. Patients with respiratory longCOVID had 54% higher risk of BF than those without respiratory longCOVID. BF associated with sleep disturbance (63% with BF vs.29% without BF, p < 0.0001), shortness of breath (46% vs.18%, p < 0.0001), weakness (49% vs.22%, p < 0.0001), dysosmia/dysgeusia (12% vs.5%, p < 0.004), activity limitations (p < 0.001), disability/leave (11% vs.3%, p < 0.0001), worsened perceived health since acute COVID-19 (66% vs.30%, p < 0.001) and social isolation (40% vs.29%, p < 0.02), despite no differences in premorbid comorbidities and age. Conclusions and relevance A year after COVID-19 infection, BF persists in a third of patients. COVID-19 severity is not a predictive risk factor. BF associates with other longCOVID and independently associates with persistent debility.